Get personalized and accurate responses to your questions with IDNLearn.com. Get the information you need from our experts, who provide reliable and detailed answers to all your questions.

Screenshot below will hold the question.

Screenshot Below Will Hold The Question class=

Sagot :

The equation the completes the proof in step 6 is m<w + m<x = m<x + m<z

How to complete the proof?

In step 4 of the proof, we have the following equation

m<w + m<x = m<y + m<z

In step 5, we have

m<x = m<y

When m<x = m<y is substituted to the equation in step 4, we have:

m<w + m<x = m<x + m<z

Hence, the equation the completes the proof in step 6 is m<w + m<x = m<x + m<z

Read more about mathematical proofs at:

https://brainly.com/question/1788884

#SPJ1